Velhas e novas territorialidades nas margens da barragem de Anagé-BA : da desterritorialização à reterritorialização - Rocha, Gabriela Silveira (2011)
The barrages built in the Northeast would be linked to the politic of combat against drought and advantage of regional potentialities. In this context, the building of the barrage would offer support to the implantation of irrigation system, these were thought as alternative not only to solve the hydro problem, but also to make the agrarian system more dynamic in all the northeast territory. So, the object of study is the analysis the processes of territorialization, disterritorrialization and reterritorialization occurred with the implantation of the Barrage Anagé in the state of Bahia. In this research paper the territory and its mobility has been studied, treating it as a field of strength that connects the space of production and circulation, the continuous and discontinuous territories and all the special organization of the area to be studied. The investigation had as content of understanding the process of transformation of the territory since the territorial landmark from 1980 to 2010, emphasizing ,mainly, the function of the barrage in the process of disterritorrialization and reterritorialization of those reached by the Barrage of Barrage of Anagé The research aimed to analyze the recent process of organization and use of lands around the barrage of Anagé and intends to clear situations that will purpose a better comprehension about the problem that involves the people reached by barrages with their spacial mobility, the speculation of the appropriation destined to the new use of the territory, resulting in the intervention of social movements that comes from the Movement of the Reached by (MAB),and the valorization of the space., the different kinds of appropriation and use of a territory.